2017
DOI: 10.1186/s12898-017-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing the potential significance of different scion/rootstock genotype combinations on the ecology of old cultivated olive trees in the southeast Mediterranean area

Abstract: BackgroundA previous multi-locus lineage (MLL) analysis of SSR-microsatellite data of old olive trees in the southeast Mediterranean area had shown the predominance of the Souri cultivar (MLL1) among grafted trees. The MLL analysis had also identified an MLL (MLL7) that was more common among rootstocks than other MLLs. We here present a comparison of the MLL combinations MLL1 (scion)/MLL7 (rootstock) and MLL1/MLL1 in order to investigate the possible influence of rootstock on scion phenotype.ResultsA linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Olive grafting has been reported since Classical times, particularly in Ancient Greece and Ancient Rome, and is designed to provide productive varieties with more hardy roots (in Pease, 1933). In contrast to other fruit crops, such as grape or apple (Myles et al, 2011;Cornille et al, 2014;Warschefsky et al, 2016), the intentional breeding of rootstocks is poorly documented in olive (Barazani et al, 2014(Barazani et al, , 2017. Barazani et al (2017) recently showed that scion/rootstock genotype combinations are not randomly distributed, suggesting that growers may have selected some combinations in the Levant area, possibly to improve oil quality or drought tolerance.…”
Section: Early Olive Domestication During Pre-historic Times and The mentioning
confidence: 99%
See 1 more Smart Citation
“…Olive grafting has been reported since Classical times, particularly in Ancient Greece and Ancient Rome, and is designed to provide productive varieties with more hardy roots (in Pease, 1933). In contrast to other fruit crops, such as grape or apple (Myles et al, 2011;Cornille et al, 2014;Warschefsky et al, 2016), the intentional breeding of rootstocks is poorly documented in olive (Barazani et al, 2014(Barazani et al, , 2017. Barazani et al (2017) recently showed that scion/rootstock genotype combinations are not randomly distributed, suggesting that growers may have selected some combinations in the Levant area, possibly to improve oil quality or drought tolerance.…”
Section: Early Olive Domestication During Pre-historic Times and The mentioning
confidence: 99%
“…In contrast to other fruit crops, such as grape or apple (Myles et al, 2011;Cornille et al, 2014;Warschefsky et al, 2016), the intentional breeding of rootstocks is poorly documented in olive (Barazani et al, 2014(Barazani et al, , 2017. Barazani et al (2017) recently showed that scion/rootstock genotype combinations are not randomly distributed, suggesting that growers may have selected some combinations in the Levant area, possibly to improve oil quality or drought tolerance. Elucidating ancient cultural shifts linked to the beginning of cultivated olive use and breeding is not a straightforward task (e.g.…”
Section: Early Olive Domestication During Pre-historic Times and The mentioning
confidence: 99%
“…Our results showed evidences of this cultural practice. It is likely that scion/rootstock genotype combinations are not randomly distributed, but selected by the growers to introduce genotypes with improved agronomic features and/or better adapted to the edaphoclimatic conditions, as suggested by [ 70 ]. The slightly genotypic differences found in some cases between the canopy and the basal part of the tree could be due to a real graft among clones of the same cultivar or to somatic point mutations [ 20 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, resistance to M. javanica has been reported in some olive genotypes (Palomares-Rius et al, 2019;Archidona-Yuste et al, 2020b), while crop intensification and grafting practices may have deep consequences on soil nematode communities (e.g. Warschefsky et al, 2016;Ali et al, 2017;Barazani et al, 2017). In the 17 locations here studied, Ali et al (2017) showed a slightly lower phytoparasitic nematode (PPN) richness in cultivated stands than in the wild habitat (mean: 6.0 vs. 6.4 genera/dm 3 ), while, in Finally, our study highlighted an adaptive response in an asexual parasite.…”
Section: Diverging Selection Between Habitatsmentioning
confidence: 99%